Systematic Review Shows Only Few Reliable Studies of Physical Activity Intervention in Adolescents - Nara Michelle Moura Soares; Arley Santos Leão; Josivan Rosa Santos; Glauber Rocha Monteiro; Jorge Rollemberg dos Santos; Sara Maria Thomazzi; Roberto Jerônimo dos Santos Silva (The Scientific World Journal)
Introduction. Several studies have pointed to the high prevalence of low levels of physical activity in adolescents, suggesting the need for more effective interventions for this group. The aim of this study was to present evidence of intervention programs for efficacy of physical activity for adolescents. Methods. Surveys in PubMed, SportDiscus, LiLacs, and SciELO databases were conducted using keywords to identify population, intervention, and outcome, as well as DeCS and MeSH terms in English, Portuguese, and Spanish, whenever appropriate. The review included observational studies with minimal intervention of six months, minimum sample size of 100 adolescents, written in any language, and those who have reached STROBE score greater than 70%. Results. Only seven studies met all inclusion criteria. Of these, five were pre- and postintervention and two had n>2000 participants. Interventions were of several types, durations, and strategies for physical activity implementation. Behavior change was assessed in 43% of studies and three reported success in some way. Conclusion. Due to heterogeneity in their contents and methodologies, as well as the lack of jobs that accompany adolescents after the intervention period, one cannot draw conclusions about the actual effects of the intervention programs of physical activity on the behavior of young people.